2007
DOI: 10.1556/aphysiol.94.2007.1-2.6
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 gene and endothelial nitric oxide synthase gene polymorphisms in adolescents with juvenile and obesity-associated hypertension

Abstract: Hypertension is an increasing public health problem all over the world. Essential hypertension accounts for more than 90% of cases of hypertension. It is a complex genetic, environmental and demographic trait. New method in molecular biology has been proposed a number of candidate genes, but the linkage or association with hypertension has been problematic (lack of gene-gene and gene-environment interaction). It is well known that genetic influences are more important in younger hypertensives, because children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 70 publications
2
11
1
3
Order By: Relevance
“…In a study of adolescents with obesity-associated hypertension, no association was found with T-786C promoter and VNTR polymorphisms, assisting the characteristics of our control group. 43 …”
Section: Discussionmentioning
confidence: 99%
“…In a study of adolescents with obesity-associated hypertension, no association was found with T-786C promoter and VNTR polymorphisms, assisting the characteristics of our control group. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Отже, в пацієнтів групи контролю переважає генотип Lys/Lys та алель Lys гена ЕТ-1, що відповідає резуль-татам дослідників Казахстану, Угорщини та м. Суми (Україна) [3,6,7]. У пацієнтів з ЕГ різної тяжкості та-кож превалює генотип Lys/Lys та алель Lys гена ЕТ-1, що відповідає низці інших досліджень.…”
Section: матеріали і методи дослідженняunclassified
“…носійство алелі Asn асоціюється з 3 ступенем АГ. Подібні дані отримані в роботі російських вчених (м. Москва), де досліджено, що АГ 3 ступеня асоціюється з алелю Asn гена ЕТ-1, а генотип Lys/Lys був захисним [6].…”
Section: частота зустрічальності генотипу Lys/lys і носіїв алелі Asn unclassified
“…It has been identified as a candidate gene for EH and CVD [30]. A G-to-T transversion predicting a Lysine-Asparagine change at amino acid 198 (Lys198Asn) single-nucleotide polymorphism (SNP) has been associated with increased BP levels from adolescence to middle age in Japanese EAs and AAs [3133]. The Lys198Asn SNP has also been associated with exaggerated BP reactivity to laboratory stressors, particularly within the context of background stress-related factors.…”
Section: Introductionmentioning
confidence: 99%